IMPLEMENTAÇÃO DE SORVEDOURO DE DADOS DE APLICAÇÃO IOT DE IRRIGAÇÃO AUTOMÁTICA (REMUNOM, 2024)
This work aims to describe the data sink implementation for an IoT irrigation system named Hortência, previously developed. The paper assembles a real scenario for data collecting and formatting. Moreover, it performs a requirement analysis for database implementation for this IoT application.